2019
DOI: 10.5755/j01.sace.24.1.23236
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Insulation Boards Made of Tree Bark & Hemp Residues

Abstract: Two disparate waste materials were mixed to identify the likelihood of constructing insulation boards. Treebark and Hemp (cannabis) residues were combined in different proportions and with two dissimilar typesof glue. The thermal conductivity (λ) for all boards was measured. Diverse methods of processing the finalboards demonstrated altered thermal properties based also on the different density (low and medium).The results have validated the possibility of exploiting local waste materials to produce an eco-fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…Insulation was seen as a passive strategy to reduce the energy consumption on a building, with findings revealing at least a 25.2% (straw bales) and at most a 25.8% (hemp wool) reduction in annual energy consumption. Recent studies [13,[32][33][34][40][41][42][43] also showed the correlation between energy consumption reduction and the use of the appropriate insulation material, confirming our findings, which reveal that the energy reduction depends first on the type of insulation material used. However, other parameters can affect this reduction such as the thickness of the insulation layer used.…”
Section: Importance Of Office Building Insulationsupporting
confidence: 91%
See 1 more Smart Citation
“…Insulation was seen as a passive strategy to reduce the energy consumption on a building, with findings revealing at least a 25.2% (straw bales) and at most a 25.8% (hemp wool) reduction in annual energy consumption. Recent studies [13,[32][33][34][40][41][42][43] also showed the correlation between energy consumption reduction and the use of the appropriate insulation material, confirming our findings, which reveal that the energy reduction depends first on the type of insulation material used. However, other parameters can affect this reduction such as the thickness of the insulation layer used.…”
Section: Importance Of Office Building Insulationsupporting
confidence: 91%
“…Tree bark was explored in [31] as an insulating filling material in exterior wood frame wall structures, resulting in a possible thermal insulator, while pine tree bark and cannabis residues combined with two different adhesives created boards with excellent insulating qualities [32]. Due to its low density, extremely strong thermal insulation qualities, a large percentage of cork cells, high chemical extractives content protecting against microbes, and low flammability [13,33], tree bark is appropriate for thermal insulation material.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The thermal performance of this board was also competitive with an average thermal transmittance of 0.30 W/mK when compared to existing commercial oil based insulation panels [20]. Ninikas et al studies the thermal properties of insulation boards that were made of hemp residues and tree bark [21]. However, their mechanical properties were not addressed, and the determination of the thermal conductivity was based on a different measurement setup, as described later in the paper.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis insulation panel is one of the most environmentally friendly insulation materials (Ninikas et al 2019). Cannabis comes from a fast-growing annual plant called Cannabis sativa.…”
Section: Cannabis Panelmentioning
confidence: 99%